Influence of different sizes of composite femora on the biomechanical behavior of cementless hip prosthesis. (January 2017) - Schmidutz, Florian; Woiczinski, Mathias; Kistler, Manuel; Schröder, Christian; Jansson, Volkmar; Fottner, Andreas
Abstract: Background: For the biomechanical evaluation of cementless stems different sizes of composite femurs have been used in the literature. However, the impact of different specimen sizes on test results is unknown. Methods: To determine the potential effect of femur size the biomechanical properties of a conventional stem (CLS Spotorno) were examined in 3 different sizes (small, medium and large composite Sawbones®). Primary stability was tested under physiologically adapted dynamic loading conditions measuring 3-dimensional micromotions. For the small composite femur the dynamic load needed to be adapted since fractures occurred when reaching 1700 N. Additionally, surface strain distribution was recorded before and after implantation to draw conclusions about the tendency for stress shielding. Findings: All tested sizes revealed similar micromotions only reaching a significant different level at one measurement point. The highest micromotions were observed at the tip of the stems exceeding the limit for osseous integration of 150 μm. Regarding strain distribution the highest strain reduction after implantation was registered in all sizes at the level of the lesser trochanter. Interpretation: Specimen size seems to be a minor influence factor for biomechanical evaluation of cementless stems. However, the small composite femur is less suitable for biomechanical testing since this size failed under physiological adapted loads. For the CLS Spotorno osseous integration is unlikely at the tip of the stem and the tendency for stress shielding is the highest at the level of the lesser trochanter. Highlights: For the biomechanical evaluation of cementless stems different sizes of composite femurs are used. In vitro primary stability is not affected by the size of composite femur. For all sizes there is a strong tendency for stress shielding in the proximal part of standard cementless stems.